PERLINDUNGAN HUKUM HUTAN BAKAU/MANGROVE DI WILAYAH PESISIR PANTAI TELUK BIMA - Arba, Arba; Sudiarto; Munandar, Aris (Faculty of Law, University of Mataram, 2024)
Mangrove forests, as a natural resource, are essential for human life, from economic, cultural, tourism, religious, environmental, and health aspects. This research aimed to study and analyze the forms of legal protection for mangrove forests in the coastal area of Bima Bay and to study and analyze the efforts made by the Bima City and Regency governments to protect mangrove forests along the Asakota coast. This research was empirical legal research; the methods used were the statutory, conceptual, and Socio-legal approaches. Legal materials and data sources used were from library materials consisting of primary, secondary, and tertiary legal materials and field data in the form of primary and secondary data. Analysis using descriptive qualitative. The results show that the government's legal protection of mangrove forests, including the mangrove forest areas in the coastal area of Bima Bay, includes preventive and repressive legal protection. Preventive legal protection is carried out by establishing legal rules, socializing and implementing legalÂ rules, and implementing supervision. Meanwhile, repressive legal protection is by law enforcement and legal sanctions to legal entities or individuals who use mangrove forest areas in the coastal area of Bima Bay without permission. The efforts made by the Bima City and Bima Regency governments to protect mangrove forests along the coast of Asakota are by educating people to be more aware of the contribution of mangrove forests for human life and theÂ environment;Â Carrying out rejuvenation by replanting in damaged areas and new areas along the coast of Bima Bay, as well as maintaining and protecting the existence of mangrove forests with the central government.